PHYSIO-ANATOMICAL EXPLORATION OF ROLE OF MENTAL HEALTH IN ANNAVAHA SROTAS DISORDERS - Kumar, *Nitin; Chandra Gupta, Harish; Bhatnagar, Vikash (AYUSHDHARA, 2016)
The good health is defined not only on basis of physical well being but rather also on mental well being. As told in Ayurveda texts- “Prasanna Atmendriya Manah Swasth Ityabhidheeyate”. In era of globalization, the fast & modernized lifestyle has taken toll on one’s health. Now a day, majority of population is suffering from digestive problems such as acidity, reflux, bloating, stomach pain, constipation, and anorexia. These digestive problems are mainly due to bad dietary habits like junk foods, lack of balanced diet etc and also due lack of proper sleep, stress etc. Stress shows both long term and short term effect on gut functions like gastric secretions, gut motility, mucosal permeability etc. Our Acharas were well aware about this factor for digestive disorders, as they included Shoka, Bhaya, Krodha etc. as Nidana (cause) of digestive disorders. These various Nidana of digestive disorders causes Agnidushti which is cause of Annvaha srotodushti and Mandagni. It is very important to understand the relationship between gut and mental health to know aetio-pathogenesis of disorders, which will help to develop holistic approach for better treatment of Annavaha Srotas Disorders.